Effects of copper on expression of methane monooxygenases, trichloroethylene degradation, and community structure in methanotrophic consortia. Issue 4 (22nd February 2018) - Xing, Zhilin; Zhao, Tiantao; Zhang, Lijie; Gao, Yanhui; Liu, Shuai; Yang, Xu
Abstract: Copper plays a key role in regulating the expression of enzymes that promote biodegradation of contaminants in methanotrophic consortia (MC). Here, we utilized MC isolated from landfill cover to investigate cometabolic degradation of trichloroethylene (TCE) at nine different copper (Cu 2+ ) concentrations. The results demonstrated that an increase in Cu 2+ concentration from 0 to 15 μM altered the specific first‐order rate constant k 1, TCE, the expression levels of methane monooxygenase ( pmoA and mmoX ) genes, and the specific activity of soluble methane monooxygenase (sMMO). High efficiency TCE degradation (95%) and the expression levels of methane monooxygenase (MMO) were detected at a Cu 2+ concentration of 0.03 μM. Notably, sMMO‐specific activity ranged from 74.41 nmol/(mgcell  h) in 15 μM Cu 2+ to 654.99 nmol/(mgcell  h) in 0.03 μM Cu 2+, which contrasts with cultures of pure methanotrophs in which sMMO activity is depressed at high Cu 2+ concentrations, indicating a special regulatory role for Cu 2+ in MC. The results of MiSeq pyrosequencing indicated that higher Cu 2+ concentrations stimulated the growth of methanotrophic microorganisms in MC. These findings have important implications for the elucidation of copper‐mediated regulatory mechanisms in MC.